If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -2x + 2x + 4x + -5x = 4 Combine like terms: 2x + -2x = 0 0 + 2x + 4x + -5x = 4 2x + 4x + -5x = 4 Combine like terms: 2x + 4x = 6x 6x + -5x = 4 Combine like terms: 6x + -5x = 1x 1x = 4 Solving 1x = 4 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '1'. x = 4 Simplifying x = 4
| 4x+.5(8x-6)=2(4x+3) | | 0=12b-12 | | -5j+-16j+13j=16 | | 12=3(-2-2) | | h^2+b^2=8.5-h^2 | | x^2+y^2=8.5-h^2 | | 2c-(-6)=12 | | 5x-1+1x+15=6+5x+14-2x | | b+9=8+7 | | -6x-6(-3x)=-24 | | 2y+11=6-y | | (3k+1)x^2+2x=1 | | 7v+2(v-2)=-22 | | t*5-7=10 | | -5(2r+4)=10 | | -9x+-20x+19x+5x-(-9x)=-12 | | -6x+4x=14 | | 6t-3t-3t+3t=18 | | x*(x+1)+109=x+(x+1) | | 16t-15t=14 | | x=y-11 | | -3x-(-8x)=15 | | (8/125)-2/3 | | 5x-1+1x+15=6+5x+14-21 | | 19t-11t=16 | | -8x-7(-6x)=0 | | y=50+15x | | 9q-3q=6 | | -5h-3-7h=-171 | | 10+5u=-21 | | 2c-4=14c-10 | | 4(y+5)-y=35 |